Analisis Kepuasan Nasabah pada Kualitas Pelayanan dengan Metode Fuzzy Service Quality dan Quality Function Deployment di PT Bank Mandiri - Ginting, Yeni Yuswita; Siregar, Ninny; Delvika, Yuana (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2022)
Service quality is the most important factor for the bank so that the Bank can keep surviving and developing. Every day the number of customers development is increasing so that the service quality and customer satisfaction must be prioritized. The way to improve service quality is trying to find out customers' desires, where the Fuzzy Servqual (Service Quality) and QFD (Quality Function Deployment) methods were used in improving the quality of bank services. The purpose of this research was to design a service improvement proposal at Bank Mandiri KCP Medan Citra Garden by using Fuzzy Servqual and QFD. In this study, a survey was conducted by distributing questionnaires to 100 respondents from Bank Mandiri KCP Medan Citra Garden based on data processing performed using the Fuzzy Servqual method, for designing improvement proposals using the Quality Function Deployment (QFD) method. The level of customer satisfaction at Bank Mandiri KCP Medan Citra Garden was lower than the importance level of affected factors in customer satisfaction at Bank Mandiri KCP Medan Citra Garden which needed to be more improved was the Tangible dimension (Physical Evidence) shown in the comfort and security of the location and parking lot provided with a score of -13.17. Furthermore, that had to be maintained on the Tangible dimension (Physical Evidence) was shown in the bank officers' appearances who were always neat and wore masks and gloves with a score of 4.496 at Bank Mandiri KCP Medan Citra Garden. Thus, it was recommended to Bank Mandiri KCP Medan Citra Garden to further improve service performance on all services.